Simultaneous surgery for gastrostomy and laryngotracheal separation in a patient with Tay‒Sachs disease - Masaharu Moroto; Uda Daisuke; Tomoya Yodoi; Yoshihiro Nitta; Yohei Sugimoto; Tomohiro Chiyonobu; Hiroyuki Yamada; Kayo Ozaki; Taichi Nakatani; Norio Sakai (Human Genome Variation)
Abstract Genetic testing identified novel compound heterozygous missense variants in the HEXA gene (NM_00520.6: c.775A>C and NM_000520.6: c.508C>T) in a 16-month-old girl diagnosed with Tay‒Sachs disease. The patient gradually became unable to consume food orally. She suffered severe aspiration pneumonia and underwent gastrostomy and laryngotracheal separation at 2 years and 4 months of age. Despite an initially good prognosis, she died at 3 years of age.